Combination of Curcuma (Curcuma xanthorriza Roxb) and Awar-awar (Ficus septica Burm.F.) Ethanolic Extracts Enhance Doxorubicin to Modulate Cell Cycle Progression of T47D Cells - Laili Nailul Muna; Riris Istighfari Jenie (Indonesian Society for Cancer Chemoprevention, 2018)
One of the efforts to cure breast cancer is a combination of the chemotherapeutic agent with medicinal plants. This study was conducted to examine the activity of the combination between doxorubicin, curcuma rhizome (Curcuma xanthorriza Roxb.) ethanolic extract (CEE), and awar-awar leaves (Ficus septica Burm.f.) ethanolic extract (AAE) in inducing apoptosis and modulating the cell cycle progression in breast cancer T47D cells. The combination activity was performed using three series of concentration, 1/3; 1/6 and 1/12 of IC50, The combination index (CI) of doxorubicin, CEE and AEE was determined under MTT assay. The result showed that the combination of 10 µM, 5 µg/ml, 1 µg/ml concentrations of doxorubicin, CEE and AEE respectively result in synergistic effect with CI values less than 1. The treatment exhibited the cell accumulation in S phase (27.7%) against T47D breast cancer cells confirmed through cell cycle examination by flow cytometry. These results provided the evidence that CEE and the AEE can be developed as co-chemotherapeutic agents combined with doxorubicin to improve the effectiveness of breast cancer treatment.Keywords : Curcuma xanthorriza Roxb., Ficus septica Burm.f., doxorubicin, cell cycle.